Malocclusion and early orthodontic treatment requirements in the mixed dentitions of a population of Nigerian children - Oluranti Olatokunbo daCosta; Elfleda Angelina Aikins; Gerald Ikenna Isiekwe; Virginia Efunyemi Adediran (Wolters Kluwer Medknow Publications, 2016)
Introduction: The aims of this study were to establish the prevalence of dental features that indicate a need for early intervention and to ascertain the prevalence of different methods of early treatment among a population of Nigerian children in mixed dentition. Methods: Occlusal relationships were evaluated in 101 children in mixed dentition between the ages of 6 and 12 years who presented at the Orthodontic Unit, Department of Child Dental Health, Lagos University Teaching Hospital over a 2 years period. The need for different modes of early orthodontic treatment was also recorded. Results: Anterior tooth rotations (61.4%) and increased overjet (44.6%) were the most prevalent occlusal anomalies. Others included deep bite (31.7%), reverse overjet (13.9%), and anterior open bite (14.8%). Severe maxillary spacing and crowding were exhibited in 12.0% and 5.0%, respectively. About a third (35.7%) of the subjects presented with crossbite while lip incompetence was observed in 43.6% of the subjects. About 44% of the subjects also presented with various oral habits with digit (15.8%) and lip sucking (9.9%) being the most prevalent. Subjects were recommended for treatment with 2 by 4 fixed orthodontic appliances (22.3%), habit breakers (20.7%), removable orthodontic appliances (16.5%), and extractions (15.7%). Conclusions: Increased overjet and anterior tooth rotation were the majority of occlusal anomalies seen, which are not only esthetically displeasing but may also cause an increased susceptibility to trauma to these teeth. Treatment options varied from extractions only to the use of appliance therapy.